Community structure and environmental suitability of zooplankton in the coastal waters of Lhokseumawe City, Indonesia - Yudho Andika; Erlangga Erlangga; Erniati Erniati; Imanullah Imanullah; Imamshadiqin Imamshadiqin; Syahrul Ramadansyah (Universitas Malikussaleh, 2026)
Zooplankton or animal plankton, is an organism that is generally small in size whose life is swayed by currents in the free ocean. Banda Sakti District, Lhokseumawe City is a coastal area with potential for the study of its coastal waters, which have not been extensively explored. The purpose of this study was to assess the zooplankton community structure—including abundance, diversity, uniformity, and dominance in the coastal waters of Banda Sakti District, and to evaluate water quality conditions in relation to their suitability for supporting zooplankton life. The research was conducted in December 2021 in the coastal waters of Banda Sakti District, Lhokseumawe City, using a purposive sampling method. A total of 50 zooplankton species representing 10 phyla were identified. The total abundance of zooplankton in this study ranged from 105.55 – 140.27 ind/L. In this study, the diversity index value ranged from 22.14 to 2.77, the uniformity index ranged from 0.65 to 0.79, and the dominance index ranged from 0.04 to 0.05. Overall, water quality parameters indicated that the coastal waters of Banda Sakti District remain within suitable conditions to sustain zooplankton communities according to established environmental standards.